2020
DOI: 10.1103/physrevlett.124.087701
|View full text |Cite
|
Sign up to set email alerts
|

Optical Transistor for Amplification of Radiation in a Broadband Terahertz Domain

Abstract: We propose a new type of optical transistor for a broadband amplification of THz radiation. It is made of a graphene-superconductor hybrid, where electrons and Cooper pairs couple via Coulomb forces. The transistor operates via the propagation of surface plasmons in both layers, and the origin of amplification is the quantum capacitance of graphene. It leads to THz waves amplification, the negative power absorption, and as a result, the system yields positive gain, and the hybrid acts like an optical transisto… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 88 publications
0
7
0
1
Order By: Relevance
“…The demonstration of Stark ladders and coherent Bloch oscillations 13 paved the way for SSL multipliers (SSLMs) to provide radiation up to the 54th harmonic at 8.1 THz as well as for their use in heterodyne detection with applications to high-resolution spectroscopy 14 , 15 . Compact high performance superlattice electron devices (SLEDs) have recently reached a record room temperature 4.2 mW power output in the fundamental mode at 145 GHz 16 and synchronization between SSLs leads to a dramatic increase in output power 2 . In both cases there are propagating charge domains that produce powerful high-frequency GHz radiation and which are triggered by negative differential conductivity (NDC).…”
Section: Introductionmentioning
confidence: 99%
“…The demonstration of Stark ladders and coherent Bloch oscillations 13 paved the way for SSL multipliers (SSLMs) to provide radiation up to the 54th harmonic at 8.1 THz as well as for their use in heterodyne detection with applications to high-resolution spectroscopy 14 , 15 . Compact high performance superlattice electron devices (SLEDs) have recently reached a record room temperature 4.2 mW power output in the fundamental mode at 145 GHz 16 and synchronization between SSLs leads to a dramatic increase in output power 2 . In both cases there are propagating charge domains that produce powerful high-frequency GHz radiation and which are triggered by negative differential conductivity (NDC).…”
Section: Introductionmentioning
confidence: 99%
“…Despite the substantial success in current approaches to decrease the THz light reflection, obtaining surfaces with 100% anti-reflection and transmission rates still remains one of the main obstacles in the construction of perfect optical devices such as flat Veselago-Pendry lenses. Current advances in 2D materials have demonstrated that fabrication of hybrid structures made up of graphene and superconductors can lead to a significant enhancement in light sensitivity [2]. Similar trends have been observed in graphene covered by a thin film of colloidal quantum dots, where extremely strong photoelectric effect provides enormous gain for photo-detection (about 10 8 electrons per photon) [3].…”
Section: Introductionmentioning
confidence: 71%
“…Recent innovations in thin film technology have shown that heterostructures made of graphene and superconductors can be used effectively to amplify and generate THz waves [2,6,7]. Such heterostructures are unique objects that utilise the principles of vacuum solid-state nano-electronics for the amplification and detection of THz waves.…”
Section: Introductionmentioning
confidence: 99%
“…Other examples of hybrid Bose-Fermi systems comprise electron gas -superconductor [25][26][27] , exciton gas -2D electron gas (2DEG) 28 , and exciton-polaritons in a microcavity -2DEG systems 29 . From that perspective, a superconductor in the fluctuating regime can be looked at as a hybrid Bose-Fermi system, where two gases described by different quantum statistics coexist in one (same) 2D layer, forming a Bose-Fermi mixture.…”
Section: Introductionmentioning
confidence: 99%